Exploring the barriers and facilitators of accessing and utilising mental healthcare for adults with childhood trauma : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Psychology at Massey University, by Distance, Aotearoa/New Zealand - Brocas, Caitlin (Massey University, 2025)
Childhood trauma is a prolific and pervasive issue, with New Zealand reporting a concerning number of child maltreatment cases each year. Extensive research has highlighted the myriad of negative physiological, neurological, and psychological impacts associated with experiencing trauma in childhood. Despite this, mental healthcare service usage in New Zealand remains relatively low, with the most recent data estimating only 2.9% of the population access some form of mental healthcare annually (Te Whatu Ora, 2023). To understand this, disconnect, the current study aimed to explore the lived experiences of adults with childhood trauma and identify the barriers and facilitators that impact accessing and utilising mental healthcare. Employing Interpretive Phenomenological Analysis, semi-structured interviews were conducted with four adult participants to provide an in-depth understanding of their experiences accessing care. Analysis revealed six overarching themes: Constraints of Living in a Small Town, The Cost of Care, Confronting Internal Barriers, reaching a Breaking Point and A Need for A System that Cares. From these themes, six primary barriers were identified: Limited Resources, Incompatibility in the Therapeutic Relationship, Lack of Anonymity, Stigma, Lack of Trust and Financial Constraints. Three key facilitators also emerged: Crisis as a Motivator, Support and Positive Healthcare Relationships. Additionally, participants identified several systematic changes that would facilitate future access and utilisation of care. This thesis addresses critical gaps in existing literature and contributes to our understanding of the challenges and supports that impact to mental healthcare for adults with childhood trauma in New Zealand.
Keywords: 520304 Health psychology; 420313 Mental health services